Antibodies Against Glutamic Acid Decarboxylase 65 Are Locally Produced in the CSF and Arise During Affinity Maturation - Biljecki, Michelle; Eisenhut, Katharina; Beltrán, Eduardo; Winklmeier, Stephan; Mader, Simone; Thaller, Anna; Eichhorn, Peter; Steininger, Philipp; Flierl-Hecht, Andrea; Lewerenz, Jan; Kümpfel, Tania; Kerschensteiner, Martin; et al. (Neurology, Neuroimmunology and Neuroinflammation, 2023)
BACKGROUND AND OBJECTIVES: Antibodies (Abs) against the cytoplasmic protein glutamic acid decarboxylase 65 (GAD65) are detected in patients with neurologic syndromes together referred to as GAD65-Ab spectrum disorders. The response of some of these patients to plasma exchange or immunoglobulins indicates that GAD65-Abs could contribute to disease pathogenesis at least at some stages of disease. However, the involvement of GAD65-reactive B cells in the CNS is incompletely understood. METHODS: We studied 7 patients with high levels of GAD65-Abs and generated monoclonal Abs (mAbs) derived from single cells in the CSF. Sequence characteristics, reactivity to GAD65, and the role of somatic hypermutations of the mAbs were analyzed. RESULTS: Twelve CSF-derived mAbs were generated originating from 3 patients with short disease duration, and 7/12 of these mAbs (58%) were GAD65 reactive in at least 1 detection assay. Four of 12 (33%) were definitely positive in all 3 detection assays. The intrathecal anti-GAD65 response was polyclonal. GAD65-Abs were mostly of the IgG1 subtype and had undergone affinity maturation. Reversion of 2 GAD65-reactive mAbs to their corresponding germline-encoded unmutated common ancestors abolished GAD65 reactivity. DISCUSSION: GAD65-specific B cells are present in the CNS and represent a sizable fraction of CSF B cells early in the disease course. The anti-GAD65 response in the CSF is polyclonal and shows evidence of antigen-driven affinity maturation required for GAD65 recognition. Our data support the hypothesis that the accumulation of GAD65-specific B cells and plasma cells in the CSF is an important feature of early disease stages.
CRIS-Team Scopus Importer:2023-05-19